PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. NAGAMAS AGRO MULIA TALIKUMAIN KAB. ROKAN HULU - Pane Indriani; Indarti Sri; Hendriani Susi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of occupational health and safety (K3), workenvironment, and work motivation on employee performance at PT. Nagamas Agro MuliaTalikumain Kab. Rokan Hulu. The population in this study includes all employees at PT.Nagamas Agro Mulia Talikumain Kab. Rokan Hulu, totaling 86 people.Primary datawere collected using a questionnaire as an instrument to prove the results of the study, totest the hypothesis in this study using multiple analysis methods and path analysis withthe help of the SPSS program. The sampling technique that has been selected is thesaturated sampling technique by conducting a census. The results showed that: 1)occupational health and safety had a significant effect on employee performance, 2) workenvironment had a significant effect on employee performance, 3) occupational healthand safety had a significant effect on work motivation, 4) work environment had asignificant effect on motivation, 5) work motivation has a significant effect on employeeperformance, 6) work motivation does not mediate the effect of occupational health andsafety on employee performance, 7) work motivation does not mediate the influence of thework environment on employee performance. Keywords : Occupational Health and Safety (K3), Work Environment, Work Motivation,Employee Performance